A central limit theorem for weighted sums of associated random field. Issue 1 (2nd January 2016) - Ko, Mi-Hwa
ABSTRACT: In this paper we obtain the central limit theorem for weighted sums of the form ∑1 ⩽ i ⩽ n a n, i X i, where is an array of non negative numbers such that, max 1 ⩽ i ⩽ n a n, i → 0 as n → ∞ and is a field of associated random variables with EX i = 0 and EX 2 i < ∞. As application, we give a central limit theorem for the partial sum of linear random field .